APPLICATION OF LAND EFFICIENCY AND INCLUSIVE DESIGN CONCEPTS INTHE DESIGN OF THE SENTUL VILLAGE PAVILION - Putri, Firnanda Anggraeny; P, Resti Ananda Odie; Fitriyanto, Dominikus Aditya (ADBE, 2023)
The issue of limited land requirements and the lack of attention to disability-friendly design are architectural issues that we often hear about. The need for limited land requires the concept of land efficiency and physical disability-friendly needs will lead to inclusive design. Land efficiency can be in the form of using land as necessary by maintaining green open areas. Inclusive design can be interpreted as an effort to fulfill facilities for people with physical disabilities so that they can feel the comfort of the facilities provided in the building. The importance of land efficiency and inclusive design is needed especially in public buildings, where social activities often occur. An example of a public building is a pavilion. According to Mangunwijaya, in principle the pavilion functions as an area for socializing. From the various activities that occur in the pavilion,it can be seen that the pavilion design must respond to the needs of its diverse users. Therefore, this research aims to examine the application of the concept of land efficiency and inclusive design in the sentul village pavilion. To find out this, data collection is carried out using qualitative methods, through literature studies, and comparing the design of the Sentul Village pavilion with the usual pavilion standards. From these results we can find out the suitability of the concept of land efficiency and inclusive design applied to the design of the Sentul Village pavilion.